CostumeRentals, LLC - Oster, Sharon M., (SAGE knowledge. Cases., 2016)
Maribeth Hite, Costume Director at the Guthrie Theater Foundation (GTF), sat in her office in the summer of 2003 preparing for the next advisory board meeting of CostumeRentals (CR). A joint venture between two Minneapolis/St. Paul area professional theaters, GTF and the Children's Theatre Company (CTC), CR drew on the combined costume inventories of the two companies to allow for a nationwide rental business. A year after the partnership was established, rental volume was growing steadily, but the venture was still running a deficit. Hite knew that the directors of the two partnering theaters were concerned about continuing to fund the venture's losses, and that they would have to review the benefits that the theaters stood to gain after making it through the startup phase. This case study discusses this topic.